Instrumentation Strategies for Early Onset Scoliosis: Current Concept Review - Anari, Jason; Tuason, Dominick; Flynn, John; Akbarnia, Behrooz (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Nonoperative and operative management for early onset scoliosis has changed significantly since the Harrington era 50 plus years ago. Surgeons learned quickly that a spine fusion in the growing child can result in a short thorax and the development of thoracic insufficiency syndrome. Techniques were developed and refined over the subsequent decades to allow for spinal growth, control spine and chest wall deformity, and limit pulmonary demise. This “growth-friendly” concept is the modern-day approach to management of early onset scoliosis. In this article, we review the history of growth-friendly instrumentation following the Harrington era and present the authors preferred techniques for both growth guidance and posterior distraction-based management of early onset scoliosis.